A voz da consciência na obra Ser e tempo de Martin Heidegger - Falleiros Junior, Javert (2023)
The dissertation focuses on the theme of the voice of conscience in Martin Heidegger’s philosophical thought. We examine the voice of conscience in the work “ Being and Time”, published in 1927, one of the most important philosophical works of the 20th century due to its resonance in contemporary Western thought. To understand the being of the human being, Heidegger needed to depart from and go beyond Edmund Husserl’s phenomenological method, inaugurating the fundamental ontological method. The purpose of “Being an Time” is to analyze the question of the meaning of being. To do so, analyzing the voice of conscience is indispensable for the possibility of understanding the question of the meaning of being. The methodology of this dissertation is existential phenomenology. The research articulates the voice of conscience with the existential terms of “Being and Time” such as being-own and being-improper, guilt and existential responsibility, being-toward-death and care. We consider the voice of conscience as a hermeneutic key to the question of the meaning of being because it combines both openness to the future, grounded in the affective tonality of anxiety, and also opens up the past in the affective tonality of guilt